2021
DOI: 10.1080/21655979.2021.2003667
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs and their bioengineering applications for neurological diseases

Abstract: Engineering of cellular biomolecules is an emerging landscape presenting creative therapeutic opportunities. Recently, several strategies such as biomimetic materials, drug-releasing scaffolds, stem cells, and dynamic culture systems have been developed to improve specific biological functions, however, have been confounded with fundamental and technical roadblocks. Rapidly emerging investigations on the bioengineering prospects of mammalian ribonucleic acid (RNA) is expected to result in significant biomedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 262 publications
0
12
0
Order By: Relevance
“…Previous studies have showed that non-coding RNAs plays important roles in neurological diseases [ 23 ]. Recently many lncRNAs have been implicated in regulation of the pathogenesis of Parkinson’s disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that non-coding RNAs plays important roles in neurological diseases [ 23 ]. Recently many lncRNAs have been implicated in regulation of the pathogenesis of Parkinson’s disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA functional studies and translational research have been dominated by using chemo-engineered mimics or analogs synthesized in vitro that are literally different from natural miRNA molecules produced and folded in living cells in vivo [ 7 , 31 , 32 , 71 , 72 ]. The new hBERA/miR-34a molecule utilized in the current study was made through in vivo fermentation production, which is a novel RNA bioengineering platform technology permitting large-scale, high-yield, and cost-effective manufacture of miRNA agents [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A key challenge remains the identification of novel predictors of BC progression and the identification of new targets for interventional drug development efforts. Based on their length, non-coding RNAs can be classified as small non-coding RNAs (< 1200 nucleotides) or lncRNAs (> 200 nucleotides) [ 4 , 7 ]. Many recent studies have documented essential roles for lncRNAs as regulators of gene expression at the transcriptional, translational, and epigenetic levels in both physiological and pathogenic situations [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of high-throughput sequencing technologies has led to an increasing focus on the biological role of non-coding RNAs (ncRNAs). Protein-coding gene sequences make up just 2% of the genome, however, the other 75% is thought to be translated as noncoding RNAs (ncRNAs) [ 4 , 5 ]. Long ncRNAs (lncRNAs) are over 200 nucleotides in length and lack protein-coding potential [ 6 ].…”
Section: Introductionmentioning
confidence: 99%